(untitled) (Global Journal of Science Frontier Research, 2020)
In this paper we obtain Euler-Lagrange equations for quantum and classical mechanics by means of a canonical local basis ð‘ð‘, ð‘®ð‘® of V that they defined on a generalized quaternionic ð‘²ð‘²ð’‚ð’‚Ìˆð’‰ð’‰ð’‰ð’‰ð’‰ð’‰ð’‰ð’‰ manifold (M, g, V).